The relationship between services cape elements and customer satisfaction in a shopping mall the case of Suria KLCC Mall / Faizattul Dara Naquiah Mohd Faizal and Sharmin Baba - Mohd Faizal, Faizattul Dara Naquiah; Baba, Sharmin (Faculty of Business and Management, 2013)
This paper seeks to empirically examine the relationship between Servicescapes and Customer Satisfaction in a Shopping Mall, the top shopping mall in Kuala Lumpur; Suria KLCC mall was used for this purpose. Data were collected from a sample of 130 visitors who had visited Suria KLCC over a specified time period. This study showed that servicescapes elements do affect customer satisfaction visiting the mall. However this study only covers single case study in Suria KLCC therefore limiting the generalisibility of the finding. The results of the study indicate that practitioners should indicate the most influence servicescapes elements towards customer to foster the customer satisfaction when visiting the malls. This study addresses an identified need to further examine the connection of servicescapes in shopping malls and customer satisfaction. Moreover this study is valuable to retail industry by identifying the most influenced elements of servicescapes that affect customer satisfaction when visiting a mall.